2020
DOI: 10.1177/1741143220933903
|View full text |Cite
|
Sign up to set email alerts
|

School leadership for civic learning: The case of socio-political turbulence in Hong Kong

Abstract: Currently, the challenges deriving from the complex and dynamic socio-political context in Hong Kong influence principals’ and teachers’ relationships and interactions. Academic autonomy in Hong Kong secondary schools is not simply granted by the principals, it is influenced by the society, school conditions and key stakeholders. This study employed qualitative methods to examine how principals negotiate the political context surrounding citizenship education and how these practices influence the civic learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A fourth strand of research has payed particular attention to the role of formal leadership in promoting democracy and social justice in schools (e.g., Alviar-Martin et al, 2008;Szeto, 2020;Wong et al, 2020). Studies within this strand have critiqued the largely conceptual nature of existing studies on the enactment of social justice in schools (Berkovich, 2014;Szeto, 2020), and have addressed practices of leadership in the work with social justice.…”
Section: Research On Education For Democracy and Related Fieldsmentioning
confidence: 99%
See 2 more Smart Citations
“…A fourth strand of research has payed particular attention to the role of formal leadership in promoting democracy and social justice in schools (e.g., Alviar-Martin et al, 2008;Szeto, 2020;Wong et al, 2020). Studies within this strand have critiqued the largely conceptual nature of existing studies on the enactment of social justice in schools (Berkovich, 2014;Szeto, 2020), and have addressed practices of leadership in the work with social justice.…”
Section: Research On Education For Democracy and Related Fieldsmentioning
confidence: 99%
“…Studies within this strand have critiqued the largely conceptual nature of existing studies on the enactment of social justice in schools (Berkovich, 2014;Szeto, 2020), and have addressed practices of leadership in the work with social justice. For example, studies have demonstrated that during turbulent sociopolitical times, teachers experience difficulty addressing controversial issues and thus tend to avoid controversial topics, especially when school leaders lack a clear vision of citizenship education (Alviar-Martin et al, 2008;Wong et al, 2020). Moreover, a study by Szeto (2020) has demonstrated how principals' practices of democratic leadership occurs through responding to social justice challenges by cultivating an inclusive school environment to ensure equitable participation in school activities, fulfilling the needs of every student, motivating teaching teams' potential at different levels of hierarchy in the school, as well as establishing a mutual understanding with community stakeholders based on their personal morality and professional ethics.…”
Section: Research On Education For Democracy and Related Fieldsmentioning
confidence: 99%
See 1 more Smart Citation